Second-hand online luxury : how to succeed in the german market - Schulte, Claudia Gabriele (2020)
Second-hand online luxury is a fast-growing sector in resale business, even though it is still consid-ered in its infancy. Many predictions prognose a profitable future, thus the aim of this dissertation is to analyze the German market in online luxury second-hand, in order to propose appropriate approaches for improving the current business strategies. In particular, it analyzes the existing chal-lenges and limitations of the market in order to compile suitable resolution methods. For the exam-ination, a qualitative and quantitative approach in the design of an interview and survey research was conducted. Our findings report that consumers value particularly the physical condition, authenticity and price-quality ratio of online luxury resale products. Their main motivations deal with lower prices, good depreciation rate, as well as uniqueness and lifestyle. Detected challenges and lim-itations of the German market are classified in cultural stigma, fear of counterfeit authenticity, the German market and digitalization. To succeed better in the business, these challenges should be overcome by the creation of partnerships through a linkage of offline and online channels. Additionally, an implementation of a luxury online service and more detailed information of the product on online platforms is suggested. The research is dedicated to managers and marketers and aims to contribute to the fast-growing online luxury resale business in the German market.